RECYCLING OF PHOSPHORUS AND AMMONIA NITROGEN FROM DIGESTATE - Calábková, Katrin; Malíková, Petra; Heviánková, Silvie; Červenková, Michaela (GeoScience Engineering, 2018)
Digestate from biogas plants, formed by dewatering anaerobically stabilized sludge, is characteristic of high concentrations of phosphates and ammonia nitrogen suitable for further use. Phosphorus is an element widely used to produce fertilizers, and because of its continually shortening natural supplies, recycling of phosphorus is gaining on significance. Both phosphorus and nitrogen are important elements and their presence affect the quality of water resources. Both elements can contribute to eutrophication. At the same time, both phosphorus and ammonia nitrogen, are important elements for agricultural production, and therefore greater demands are being made in the effort to connect sewage treatment processes and the process of recycling of these nutrients. A suitable product of phosphorus and ammonia nitrogen are phosphates in the form of a structurally-poorly soluble precipitate of magnesium ammonium phosphate (struvite). This form of slowly decomposing fertilizer is distinguished by its fertilizing abilities. Compared to direct use of digestate as a fertilizer, struvite is more stable and can gradually release ammonia nitrogen for a long time without unnecessary losses. In the reported experiments, the precipitation efficiency of the recycling of ammonia nitrogen and phosphorus from the digestate liquor (liquid discharge from digestate) was, at a stoichiometric ratio of Mg2+: NH4+: PO43- (3.2: 1: 0.8) and a stirring time of 15 minutes, 87 % for ammonia nitrogen ions. Keywords: digestate, biogas plants, ammonia recovery, precipitation https://doi.org/10.2478/gse-2018-0020